FUZZY EXPERT SYSTEM UNTUK MEMBANTU DIAGNOSIS AWAL SINDROMA METABOLIK - Supardianto Supadianto; Sri Kusumadewi; Linda Rosita (Jurnal Informatika dan Rekayasa Elektronik, 2021)
Metabolic syndrome is a condition that occurs in a person simultaneously, such as an increase in blood pressure, high blood sugar levels, excess fat around the waist, and an unusual increase in cholesterol levels. This condition makes the risk for sufferers experiencing heart disease, stroke, and diabetes mellitus very high. Metabolic syndrome is a non-contagious disease. A person who has metabolic syndrome is usually difficult to detect, because experts are needed to analyze it. Fuzzy Expert System (Fuzzy Expert System) is part of artificial intelligence using fuzzy logic. where the system tries to adopt human knowledge to computers so that computers can solve problems as usually done by experts. Where later the results of the system developed in the study can at least help experts (doctors) in providing conclusions on the risk of disease suffered by patients through the analysis of metabolic syndrome. This system will involve experts such as doctors and patients, where the doctor makes a diagnosis of the patient's metabolic syndrome analysis results, and the patient is used to seeing the diagnosis of the risk of the disease being suffered.